Agranulocytosis induced by metamizole and its management with granulocyte growth factor - Čeleketić Dušica; Trpković Andreja; Cvetković Zorica (Vojnosanitetski Pregled)
Drug-induced agranulocytosis was defined as a severe selective neutropenia caused by an unexpected drug reaction. Metamizole was the most common nonopioid analgesic drug associated with agranulocytosis. It was also associated with combined blood dyscrasias and other severe immunologic disorders. The risk of agranulocytosis by metamizole seemed to be considerably higher than estimated formerly. Modern management with broad-spectrum antibiotics and haematopoietic growth factors reduced the mortality in those patients. Two cases of agranulocytosis caused by metamizole were reported.